Cross-cultural adaptation and validation of the short nutritional literacy scale for young adults (18-35years) and analysis of the influencing factors - Yaoyao Liu; Lei Zhang; Kaiyan Xu; Yiqian Ding; Fangyan Li; Tinglin Zhang (BMC, 2024)
Abstract Objectives This study translated the short nutrition literacy scale for young adults (18-35 years) into Chinese, examined its reliability and validity, and analyzed its influencing factors. Methods The scale was translated using a modified Brislin translation model. A convenience sample of 508 cases was selected for the survey. Content validity, structural validity, Cronbach's alpha coefficient, and test-retest reliability were used to evaluate the scale's reliability and validity. To screen the factors influencing nutrition literacy in young people. Results The Chinese version of the Item-Level Content Validity Index (I-CVI) was 0.833 ~ 1, and the Scale-Level Content Validity Index/Average (S-CVI/Ave) was 0.908. The cumulative variance contribution of the scale was 51.029%, and the model was generally well-fitted. The Cronbach's alpha coefficient and retest reliability of the scale were 0.826 and 0.818. The results showed that the level of education, mother's education, nutrition-related courses, and frequency of attention to nutritional health information were the factors influencing the nutritional literacy of young people. Conclusion The Chinese version of the S-NutLit Scale can effectively assess the nutrients of young Chinese people. Low levels of education, low levels of education of mothers, lack of exposure to nutrition-related courses, and low frequency of attention to nutritional health information can lead to lower levels of nutritional literacy among young people.